ANALISIS PELAKSANAAN PROGRAM TRIPEL ELIMINASI DI PUSKESMAS - Pratama Putra, Bayu; Nilam Sari, Atriany; Mauludiyah, Zaida; Noorma, Nilam; Herliani, Deska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The health problems currently being faced by Indonesia are infectious diseases such as HIV/AIDS, Syphilis and Hepatitis B. Initial surveys and document searches have been conducted. In general, it was found that the implementation of the transmission elimination program at Puskesmas Tenayan Raya had not been effective. The purpose of the study was to analyze the implementation of the triple elimination program at the puskesmas. Qualitative research with a descriptive approach. The research was conducted at Tenayan Raya Health Center in 2022. The research instrument used interview guidelines. The results showed that the implementation of the triple elimination program at Tenayan Raya Health Center has been running, but there are still limitations or components that are not in accordance with SOPs such as human resources, budgets and facilities and infrastructure, so it is recommended that related agencies need to increase the competence of health workers in the implementation of triple elimination through socialization and training activities.Keywords: Elimination, HIV, Health Center